2001
DOI: 10.1029/2000ja000069
|View full text |Cite
|
Sign up to set email alerts
|

Drift mirror instability revisited, 1, Cold electron temperature limit

Abstract: Abstract. Linear theory of the drift-mirror instability in high-/• plasma is reconsidered referring to basic principles for the two cases of a one-and a twocomponent ion plasma in presence of a cold electron background. In both cases the cold electrons serve to shortcut the parallel electric field component which imposes the condition of vanishing the field-aligned current. The corresponding low-frequency dispersion relation is derived in the fluid approximation as well as from kinetic theory including nonvani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 37 publications
(22 reference statements)
2
46
1
Order By: Relevance
“…In the case of the magnetosheath the mirror mode waves are often observed, and the existence of www.ann-geophys.net/24/2441/2006/the drift mirror mode has been expected. The drift mirror mode, however, propagates perpendicular to the density gradient direction (Hasegawa, 1969;Pokhotelov et al, 2001), whereas our results prefer the parallel direction. Perhaps the drift mirror mode is operating in the magnetosheath, but the frequency is proportional to logarithm of the density distribution, ω∝∇ log n, and therefore the wave drift effect would be too small to detect.…”
Section: Discussioncontrasting
confidence: 44%
“…In the case of the magnetosheath the mirror mode waves are often observed, and the existence of www.ann-geophys.net/24/2441/2006/the drift mirror mode has been expected. The drift mirror mode, however, propagates perpendicular to the density gradient direction (Hasegawa, 1969;Pokhotelov et al, 2001), whereas our results prefer the parallel direction. Perhaps the drift mirror mode is operating in the magnetosheath, but the frequency is proportional to logarithm of the density distribution, ω∝∇ log n, and therefore the wave drift effect would be too small to detect.…”
Section: Discussioncontrasting
confidence: 44%
“…1 is very similar to mirror wave structures observed in the magnetosheath (Balikhin et al, 2003Chisham et al, 1999). Comprehensive theory of mirror instability that accounts for electron temperature (Pokhotelov et al, 2000), finite Larmor radius effects (Pokhotelov et al, 2004), plasma gradients (Pokhotelov et al, 2001), non-Maxwellian and multicomponent plasmas (Pokhotelov et al, 2008) has been developed. Analytical studies of the quasilinear and nonlinear stages of the instability demonstrated how the mirror waves can be carried by the solar wind over long distances through the mirror stable plasma.…”
Section: Introductionmentioning
confidence: 78%
“…For our study we limit consideration of perturbations of the equilibrium state having frequencies smaller than the ion cyclotron frequency wci. According to Pokhotelov et al [2001], the drift mirror mode is described by the perpendicular pressure balance condi- All perturbed values in (1) are assumed to vary both in time and space as exp(-iwt + ik. r), /•0 is the permeability of free space, w is the wave frequency, and kll are the components of the wave vector k perpendicular and parallel to the external magnetic field, fi-k,II -2•op-k,11/B2 is the ratio of perpendicular (parallel) plasma pressure to magnetic field pressure, P-k,II are perpendicular and parallel scalar pressure components, 5p_k is the variation of the perpendicular plasma pressure and 5Bii is the compressional perturbation of the magnetic field.…”
Section: With Nonzero Electron Temperaturementioning
confidence: 99%
“…Hence the given paper can be considered as an extension of our previous approach to the drift mirror instability [Pokhotelov et al, 2001], which was limited by the cold electron temperature limit, that is to the case, when Te • 0.…”
mentioning
confidence: 99%